First report of Plum bark necrosis stem pitting-associated virus in sweet cherry in Spain - Ruiz-García, Ana B.; Morán, Félix; Olmos, Antonio (The American Phytopathological Society (APS) Journals, 2019)
Plum bark necrosis stem pitting-associated virus (PBNSPaV) is a viral species that belongs to the genus Ampelovirus, family Closteroviridae. PBNSPaV was reported for the first time infecting plum trees (Prunus salicina Lindl.) in Dinuba, CA, U.S.A. (Uyemoto and Teviotdale 1996). Since then PBNSPaV has been shown to be worldwide distributed, affecting a broad range of Prunus species (Matic et al. 2010; Candresse et al. 2017; Zamorano et al. 2017). PBNSPaV has been described to infect apricot in Spain (García-Ibarra et al. 2010). In summer 2017, a survey was conducted in a small cherry growing area in the eastern region of Spain (Planes, Alicante). In the frame of this survey, one sample (P7) from a sweet cherry tree (Prunus avium), c.v. Planera, showing reddening and necrotic spots on the leaves was analysed by High throughput sequencing (HTS) on a Nextseq 500 platform. Total RNA purified from leaves was sequenced using RNAseq TrueSeq Illumina technology including viral enrichment step by ribo-depletion. Data analysis was performed using CLC Genomics Workbench 10.1.1 and Geneious 9.1.8 softwares. After a quality control step conducted by CLC, sample P7, yielded 42,683,262 pair-end HTS reads (150 nt each). A total of 6,270 contigs (average size 1,884 nt) were de novo assembled by CLC and subsequently analysed by BlastN and BlastX. This analysis showed that 8 contigs were related to PBNSPaV, indicating the presence of this virus in sample P7. Cherry virus A (CVA) was also detected in this step, with part of its genomic sequence represented in 11 contigs. Further analysis by mapping the reads against all the full length PBNSPaV sequences available in the databases was performed using Geneious software. The best mapping results were obtained using the isolate Pair-2 (KC590345) from France as reference, allowing the recovery of a 14,199 nt sequence, representing P7 isolate's almost full length genome (GenBank accession number MN228561). The nucleotide identity between P7 isolate and Pair-2 was 99,27%. In order to confirm the presence of PBNSPaV in sample P7, amplification of a partial region of the CP gene by RT-PCR was carried out using the specific primers PBN-CP-F and PBN-CP-R (Zamorano et al. 2017). The 301 bp PCR product obtained (MN240523) was sequenced by Sanger and confirmed with 100% of identity the P7 sequence recovered by HTS (excluding the primers used for amplification). A total of 24 samples collected from the same cherry growing area were tested by RT-PCR using the same primers. Seven of these samples were positive for PBNSPaV, further confirming the presence of the virus in sweet cherry in Spain. It is interesting to note that stem pitting and bark symptoms were not observed in any of the samples analysed. To our knowledge this is the first report of PBNSPaV infecting sweet cherry in Spain, contributing to a better understanding of the epidemiology and host range distribution of this pathogen.